Peran Konfederasi Kasbi dalam Menolak Undang-Undang Cipta Kerja: Penelitian - Eji Maulana; Diah Ayu Pratiwi; Endayani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
In opposing the Job Creation Law, a government policy seen as harmful to workers' rights and weakening the position of both workers and employers. The research does not only focus on individuals but also includes objects and other things involved in the social change process. The study reveals that the Job Creation Law has caused controversy since it was enacted, and KASBI, as an alternative confederation, has used various forms of struggle such as mass actions, advocacy, and building solidarity with civil society networks. The purpose of this study is to understand KASBI's role in fighting for workers' interests, the forms of mobilization used, and the challenges faced during the process of rejecting the Job Creation Law. This study uses a qualitative descriptive approach, including in-depth interviews with KASBI members and leaders, field observations during protest actions, and analysis of documents related to the policy and official statements from the organization. The findings show that KASBI is not just a platform for representing workers, but also a consistent social movement actor in expressing opposition through various forms of demonstrations, critical campaign efforts, and strategies for consolidation at the grassroots level. However, KASBI also faces several challenges such as limited resources, political pressure, and attempts at discrediting from parties that support the Job Creation Law. KASBI is a symbol of workers' resistance to free market policies in Indonesia.